Data Reproducibility and Effectiveness of Bronchodilators for Improving Physical Activity in COPD Patients - Minakata, Yoshiaki (J Clin Med, 2020)
Increasing physical activity (PA) in patients with chronic obstructive pulmonary disease (COPD) is an important issue, however, the effect of bronchodilators on PA is still controversial. The indicators of PA, as measured by an accelerometer, can easily fluctuate based on several factors, which might cause inconsistent results. In this review, we listed the indicators of PA and the factors influencing the reproducibility of indicators of PA, and reviewed reports in which the effects of bronchodilators on PA were evaluated by an accelerometer. Then, we investigated the association between the processing of influencing factors and the effectiveness of bronchodilators for improving the PA of COPD patients. Fifteen reports were extracted using the PubMed database. In all seven reports in which adjustment was performed for at least two of four influencing factors (non-wear time, data from days with special behavior, environmental factors, and number of valid days required to obtain reproducible data), bronchodilators showed beneficial effects on PA. No adjustment was made for any of these factors in any of the four bronchodilator-ineffective reports. This suggests that the processing of influencing factors to secure reproducibility might affect the results regarding the effectiveness of bronchodilators for improving PA in COPD patients.